Effectiveness of Visual Inspection with Acetic Acid and Cervical Cytology in Early Detection of Precursors of Cervical Cancer in Nepal - Dongol Singh, A.; Shakya, S.; Mudbari, J. (Kathmandu University Medical Journal, 2021)
Background Cervical cancer ranks as the first, most frequent cancer amongst Nepalese women. This can be prevented through primary prevention and early detection using screening techniques. Though cervical cytology is a standard screening tool in most of the developed countries, it fails to be the screening method of choice in low and middle income countries (LMICs) with limited resources due to financial and technical constraints. Objective This study aims at early detection of pre-cancerous lesion in cervix with cervical cytology and visual inspection with acetic acid. Method This is a hospital based, descriptive cross-sectional study. It included 104 women attending Obstetrics and Gynecology out-patient department (OPD) in Dhulikhel Hospital. Visual inspection of cervix with acetic acid (VIA) and liquid based cytology (LBC) was performed followed by cervical biopsy for positive VIA, or having abnormal cytology, or having unhealthy appearance of cervix even after treatment. Result The incidence of positive VIA and cytology screening was 38.5% and 7.7% respectively. The negative predictive value of VIA and cytology were similar whereas VIA was found to be more sensitive than cytology. Conclusion Cytology screening is used as an investigation of choice for screening of cervical cancer. In Nepal, VIA can be a good alternative for early detection of cervical cancer as it is found to be more sensitive than cytology.